Expediente - Horizonte, Belo Horizonte, v. 20, n. 61, jan./abr. 2022 - Barros, Brasil Fernandes de (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2023)
Expediente - Horizonte, Belo Horizonte, v. 20, n. 61, jan./abr. 2022